2012
DOI: 10.1007/s00405-012-2151-z
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Baha in the elderly with single-sided deafness

Abstract: The objective of this study is to determine the benefits of bone-anchored hearing aid (Baha) contralateral routing of signal (CROS) in the older adult population with single-sided deafness. Five questionnaires [general usage questionnaire, Glasgow benefit inventory (GBI), Abbreviated profile of hearing aid benefit (APHAB), Nijmegen cochlear implant questionnaire and the hearing handicap inventory for the elderly-screening version (HHIE-S)] were used to evaluate Baha use. Consecutive patients over 60 years of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
1
16
0
4
Order By: Relevance
“…Nevertheless, the results of the GBI questionnaires are similar to those obtained with the use of other bone-anchored hearing devices in SSD [Faber et al, 2013;Saroul et al, 2013].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Nevertheless, the results of the GBI questionnaires are similar to those obtained with the use of other bone-anchored hearing devices in SSD [Faber et al, 2013;Saroul et al, 2013].…”
Section: Discussionsupporting
confidence: 67%
“…Contralateral rerouting of signal (CROS) hearing aids [Bosman et al, 2003;Finbow et al, 2015;Hol et al, 2005;Wazen et al, 2003] and percutaneous bone-anchored hearing devices [Faber et al, 2013;Martin et al, 2010;Stewart et al, 2011;Zeitler et al, 2012] have been proposed for the rehabilitation of SSD with different results. More recently, cochlear implant has been suggested for the rehabilitation of SSD [Arndt et al, 2011;Erbele et al, 2015;van Zon et al, 2015;Vermeire and Van de Heyning, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence that SSD users of BAIs consistently display benefit, although performance and subjective outcomes vary [Andersen et al, 2006;Faber et al, 2013]. Benefit, satisfaction, and disability have been shown to be associated with improved performance on SIN tasks [Snapp et al, 2012], and high TA values have been suggested as limiting factors to benefitting by BAI in the SSD population [Stenfelt, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of BAIs for SSD has been well documented, but subjective benefit and satisfaction varies considerably [Andersen et al, 2006;Faber et al, 2013]. Despite this, studies regarding candidacy measures and criteria are limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation